Challenges and Pedagogical Strategies in Arabic Pegon Learning for Modern Pesantren Alumni at Islamic Universities - Alfina Habibatur Rahmah; Ahmad Maghfurin; Naifah Naifah; Nasikhin Nasikhin; Ahmad Muthohar (J-PAI: Jurnal Pendidikan Agama Islam, 2025)
This study analyzes the challenges faced by alumni of modern pesantren in understanding classical Islamic texts (Kitab Kuning) through Arab Pegon learning at Ma'had Al-Jami'ah, UIN Walisongo. Utilizing a qualitative case study design, data was collected through in-depth interviews, participatory observations, and document analysis, with validation achieved through source and method triangulation. The results indicate that Arab Pegon is systematically taught through the reading and explanation of Kitab Kuning, guided sessions with ustadz, and weekly muhadasah classes to enhance communication skills. However, alumni encounter several obstacles, such as unfamiliarity with Pegon script, which is not commonly taught in modern pesantren, difficulties in understanding its structural differences compared to formal Arabic grammar, and low motivation due to perceived irrelevance to their academic objectives. Additionally, traditional methods such as bandongan and sorogan pose challenges for students accustomed to modern educational systems. To comprehend these dynamics, this study employs an integrative pedagogical approach combining traditional and modern methods alongside sociolinguistic perspectives. To address these challenges, the strategies for teaching Arab Pegon include a gradual introduction to Pegon script, reading-writing practices with the guidance of teachers, and vocabulary memorization. This study contributes to the pedagogical integration of traditional and modern education methods while proposing a model for Arab Pegon instruction that is responsive to the diverse educational backgrounds of students.